Strategies Used in Translating a Text from Nepali to English: "A Case of Ke Nepal Sano Chha?" - Joshi, Rajendra Prasad (Journal of Research in Education, 2025)
Translation has become important in modern linguistic and cultural studies, yet it remains a difficult and most awaiting attempt. This study explores the strategies adopted by the translator in rendering the meaning of the source language (Nepali) text into the target language (English). Mainly, it observes the translation of a Nepali essay ’Ke Nepal Sano Cha?’ written by Laxmi Prasad Devkota into English text ’Is Nepal Small?’ by Govind Raj Bhattarai. I employed a corpus based research design utilizing parallel corpora of the Nepali essay into English versions of the text. The data for the study were derived from both versions of the essay, with observation serving as the primary method of data collection. The analysis identifies several frequently utilized translation strategies, including translation by more general terms, translation by neutral terms, translation using loan words with or without explanations and sense-based translation. The findings present the challenges essential in the translation process, emphasizing issues related to lexical, cultural and contextual equivalence. These findings highlighted the intrinsic difficulty achieving exact translation which resulted because of the cultural and linguistic nuances embedded in languages. The study suggested that proper translation involve a deep understanding of the source and target languages as well as their corresponding cultural contexts. These intuitions have implications for improving translation practices and strategies in future linguistic and literary endeavors.